The indispensability of good operation & maintenance (O&M) manuals in the operation and maintenance of low carbon buildings - Owajionyi, Frank L.; Omer, Siddig; Riffat, Saffa; Mempouo, Blaise (Elsevier, 2014)
Increase in energy usage, particularly from fossil fuel sources is widely understood to be responsible for the environmental problems (Climate Change) experienced globally today. Response to mitigating this anthropogenic induced consequence created the need for innovative low carbon and renewable technologies in buildings. In the UK presently, every new building is expected to be low-carbon and energy-efficient. However, it is widely acknowledged that significant differences often exist between designed and in-use performances of the buildings. Clients and end-users of these technologies appear not to be getting long term value for their investments; much attention has not been given to how these innovative technologies can be operated and maintained long into the future. Recent researches also underpin the fact that the wide information gap existing between designers and building end-users is one of the factors responsible for the performance-gap. This paper therefore presents excerpts of a research aimed at exploring a best practice approach to operability and maintainability of low-carbon-buildings. The research methodology involved the use of interviews, surveys and case study. Findings suggest that a properly prepared O&M manual is a potential document that that could bridge this gap and that it is an indispensable tool for the effective and efficient operation and maintenance of low carbon buildings.